THE EFFECT OF HONEY PINEAPPLE JUICE (Ananas comosus var. cayenne) ON TOOTH ENAMEL HARDNESS - Fadiah Annisa Safirah; Gunawan Wibisono; Ainun Rahmasari Gumay; Muflihatul Muniroh (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2020)
Background: The habit of drinking juice containing high acid in a certain time affects tooth erosion by inducing the dissolvement of enamel hydroxyapatite crystal. Honey pineapple juice is known to have a high acid content and  lower pH. However, there have been no reports of honey pineapple juice on tooth enamel hardness. Aim: To determine the effect of honey pineapple juice on tooth enamel hardness. Methods: This study used an experimental laboratory design with a pre- and post-test group design. Twenty-four post extraction maxillary or mandible premolars were divided into 4 treatment groups; where each group was immersed in honey pineapple juice for 30, 60, 90 and 120 minutes. The pH of honey pineapple juice was determined in the early treatment. The hardness test was carried out before and after the treatment using Vickers Hardness Tester with a load of 100 grams for 15 seconds. Data analysis used Wilcoxon and Kruskal Wallis test. Results: The results showed a significant differences in tooth enamel hardness before and after immersion honey pineapple juice for 30 min (p = 0.028), 60 min (p = 0.028), 90 min (p = 0.028), and 120 min (p = 0.046). There was no significant difference in the mean of tooth enamel hardness at each immersion times (p = 0.985). Conclusions: Consumption of honey pineapple juice has an effect on reducing tooth enamel hardness that could be started in a short time consumption.